Wokół metodologii wdrożeń CRM we współczesnym przedsiębiorstwie - Bembenek, Bogusław (Around Methodology of CRM Implementation in a Modern Company, 2006)
The article presents the essence of CRM, pointing out the complexity of this problem. The author concentrates on methodology of implementing CRM strategy highliting the necessity of changes in the whole organisation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 414-421